Erythroid cell-specific mRNA stability elements in the alpha 2-globin 3' nontranslated region. - Weiss, I M (1995)
Very little is known about the mechanisms mediating longevities of mRNAs. As a means of identifying potential cis- and trans-acting elements which stabilize an individual mRNA, naturally occurring mutations that decreased stability of the normally long-lived globin mRNA were analyzed. Our previous studies demonstrated that a subset of mutations which allowed the translating ribosome to read through into the alpha 2-globin 3' nontranslated region (NTR) targeted the mutant mRNAs for accelerated turnover in erythroid cells but not in several nonerythroid cell lines (I. M. Weiss and S. A. Liebhaber, Mol. Cell. Biol. 14:8123-8132, 1994). These results suggested that translational readthrough interfered with some feature of the alpha 2-globin 3' NTR required for message stability in erythroid cells. To define the cis-acting sequences which comprise this erythroid cell-specific stability determinant, scanning mutagenesis was performed on the alpha 2-globin 3' NTR, and the stability of each mutant mRNA was examined during transient expression. Three cytidine-rich regions which are required for longevity of the alpha 2-globin mRNA were identified. However, in contrast to the readthrough mutations, base substitutions in these elements destabilize the message through a translation-independent mechanism. To account for these results, we propose that the cis-acting elements form a complex or determinant in the normal alpha 2-globin mRNA which protects the message from degradation in erythroid cells. Disruption of this determinant, by translational readthrough or because mutations in an element prevent or inhibit its formation, targets the message for accelerated turnover in these cells.